1987
DOI: 10.1177/096032718700600316
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Early Postnatal Intoxication by Inorganic Mercury Resulting from the Maternal Use of Mercury Containing Soap

Abstract: A case of slight renal tubular dysfunction associated with cataract and anaemia was diagnosed in a 3-month-old black boy in whom high levels of mercury were found in blood and urine. Several arguments suggest that the renal, ocular and haematological defects may have resulted from exposure to mercury during foetal life and the 1-month lactation period due to the extensive use of inorganic mercury containing cosmetics by the mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…One study reported the effect of mercury on the reproductive system following dermal exposure [50]. It examined the case of a woman who had used a soap containing 1% mercury as mercuric iodide and a mercury containing cream during pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported the effect of mercury on the reproductive system following dermal exposure [50]. It examined the case of a woman who had used a soap containing 1% mercury as mercuric iodide and a mercury containing cream during pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Mercury can be substantially absorbed after external use and is a potential developmental toxin (Lauwerys 1987).…”
Section:  Mercury Compoundsmentioning
confidence: 99%
“…The authors explained this surprising finding with the use of mercury soap (6). A case-rapport described a child with a range of typical mercury induced birth defects and a documented extensive use of mercury soap by the mother during pregnancy and lactation (7). Several such case-reports and smaller publications do exist in the medical literature.…”
Section: By: MD Rasmus Køster-rasmussenmentioning
confidence: 99%